2018
DOI: 10.1016/j.jtho.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Early Depth of Response in Predicting Long-Term Outcome in EGFR-Mutant Lung Cancer

Abstract: The PFS advantage of EGFR-TKI over chemotherapy in advanced EGFR mutant NCLC is not explained by depth of response at 6 or 12 weeks. It should not be used as a surrogate of benefit in future trials or routine clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 36 publications
7
23
1
Order By: Relevance
“…We further analyzed the depth of response to first‐line EGFR‐TKIs and median PFS and found no significant association. Our results reiterate those of two recent studies . In a study by Wu et al, although patients who achieved a partial response had significantly longer PFS and overall survival at 16.5 and 56 weeks, respectively, higher tumor shrinkage was not related to better PFS or overall survival .…”
Section: Discussionsupporting
confidence: 89%
“…We further analyzed the depth of response to first‐line EGFR‐TKIs and median PFS and found no significant association. Our results reiterate those of two recent studies . In a study by Wu et al, although patients who achieved a partial response had significantly longer PFS and overall survival at 16.5 and 56 weeks, respectively, higher tumor shrinkage was not related to better PFS or overall survival .…”
Section: Discussionsupporting
confidence: 89%
“…Our first result is that there is no correlation between volume-based imaging biomarkers and survival. This finding is consistent with the work [12] who noticed a lack of association between tumor shrinkage and long-term survival. This illustrates why the response to TKI treatment is difficult to estimate using only the evolution of tumor volume (or RECIST).…”
Section: Discussionsupporting
confidence: 93%
“…Concerning EGFR-mutated non-small cells lung carcinoma, previous works have studied the correlations between the initial reduction of the primary tumor and the overall survival. One can find contradictory results in the literature: in [10, 11], a significant correlation has been established but more recently in [12] this correlation has not be validated using another database. Many recent studies propose to use radiomic approaches which consist in extracting a large number of quantitative features from medical images using data-characterization algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, DpR was not associated with PFS or OS in 2 studies involving patients with epidermal growth factor receptor ( EGFR ) mutations treated with EGFR tyrosine kinase inhibitors (TKIs) . Furthermore, in a pooled analysis involving patients with EGFR mutations enrolled in 5 randomized clinical trials comparing EGFR TKIs with chemotherapy, no association was found between DpR at 6 or 12 weeks and long‐term survival among patients treated with either an EGFR TKI or chemotherapy . There are several reasons for the discordant results between the chemotherapy arms from the pooled analysis and our study.…”
Section: Discussioncontrasting
confidence: 51%
“…11,12 Furthermore, in a pooled analysis involving patients with EGFR mutations enrolled in 5 randomized Cancer July 15, 2019 clinical trials comparing EGFR TKIs with chemotherapy, no association was found between DpR at 6 or 12 weeks and long-term survival among patients treated with either an EGFR TKI or chemotherapy. 13 There are several reasons for the discordant results between the chemotherapy arms from the pooled analysis and our study. Perhaps the main differences are in methodology.…”
Section: Discussionmentioning
confidence: 56%